LIGHTWEIGHT BODY STRUCTURE OF CITY BUS BASED ON TOPOLOGY OPTIMIZATION AND SENSITIVITY ANALYSIS - DING MingLiang; YAN YunBing; YANG Yong; CHEN Tao; ZHENG ZhiYang; SHEN Qi (Jixie qiangdu)
Based on the finite element thought and optimization design method,the research of lightweight on the 12 meter bus body frame of a manufacturer had been made. By establishing finite element model of the body frame,horizontal bending and torsion limit of it had been simulated. Through free modal of bus body frame simulated,static and dynamic characteristics of frame had been analyzed. Taking first order bending,torsion frequency of the frame,bending and torsional flexibility as constraint conditions and the minimum volume as the objective function,to analysis topology optimization of it. That based on the results of topology optimization,selecting 371 groups of bars as design variables to have sensitivity analysis for the frame. According to the result of topology optimization and sensitivity analysis,combining the regulation of company for finalize the design product,lightweight of body frame has been put forward,which made skeleton quality reduced by 240 kg. Compared with original frame,vibration characteristics of the new one have been maintained,and strength improved significantly. Achieving lightweight goal of the bus body frame.